Relationship between personal hygiene and manifestation of mite (Sarcoptes scabiei) in students at islamic boarding school in Sidoarjo City - Wideistianti, Annisa Pricilya; Lukiyono, Yauwan Tobing; Andini, Ary; Prayekti, Endah (Environmental and Toxicology Management, 2023)
Scabies is a disease that attacks the skin in humans, a disease caused by the mite, included in the ovoid Arthropod organism. Personal hygiene is a way to maintain health and cleanliness of the body with self-care, therefore the better a person maintains personal hygiene, the less exposure to mites that enter the skin, if someone does not maintain personal hygiene, it will be very easy to get scabies. This study aims to determine the relationship between personal hygiene and the manifestation of mites using the burrow ink test method on students at the Islamic Boarding School in Sidoarjo City. The method used is an observational type that is analytical using a cross-sectional design. A sample of 45 samples in March 2024. The sampling method was carried out using a non-probability sampling method. The samples were examined using the burrow ink test method and continued with skin scraping examination. The results of the examination of 45 samples showed that there were 9 respondents in the good category of personal hygiene clothing cleanliness with a positive scabies examination of 27 (60%) and there were 25 respondents in the poor category of personal hygiene clothing cleanliness with a negative scabies examination of 41 (91%). The results of statistical analysis from the chi-square test, the personal hygiene variable with the manifestation of mites produced a p-value = 0.157 which means there is no significant effect. In this study it can be concluded that there is no relationship between personal hygiene using the burrow ink test method and the incidence of scabies in Islamic Boarding Schools in Sidoarjo City.